Business Development of “Amma” Brand Medical Devices - Nur Utami Paulain, Annisa; Kaniawati, Keni (Journal Research of Social Science, Economics, and Management, 2024)
Good distribution of medical equipment is an important element in an efficiently functioning health system. Nowadays this business is growing up very fast as shown in numbers of registered distributors which increases in just several years. PT.AMMA Sadaya Indonesia is one of company which holding legal and permission to importing and distributing medical equipment in Indonesia since 2021. Seeing this condition the company strives to develop its business in order to expand the market and improve product quality and sales. This business plan aims to conduct a feasibility study and analyze aspects related to business development. With qualitative research methods in this business plan we analyze all these aspects. The research results show that in terms of business planning, environmental analysis, marketing aspects, operations aspects, human resources aspects, financial aspects, it appears that the AMMA company's business is worthy of development. Especially from the financial aspect, it can be seen that the results of the analysis of the R/C ratio, payback period, NPV and IRR are in the business category that is worth developing. Meanwhile, from the Timmons model analysis, design thinking, SWOT analysis and canvas business model, it can be seen how this business should be developed. SWOT analysis shows that an aggressive development strategy is the best strategy for AMMA company development.